Particle swarm optimization for maximizing lifetime of wireless sensor networks. (April 2016) - Azharuddin, Md; Jana, Prasanta K.
Abstract: Particle swarm optimization (PSO) is a popular bio-inspired algorithm which is applied to solve various optimization problems in many areas including machine intelligence, data mining, robotics and computer networks. In this paper, we propose a PSO-based scheme to solve hot spot problem caused by multi-hop communication in a cluster-based wireless sensor network. The scheme consists of routing and clustering algorithms which are shown to be energy efficient. In the routing phase, traffic load over the cluster heads (CHs) is evenly distributed, whereas in the clustering phase, we take care of all the CHs whose energy is exhausted fast by assigning lesser number of sensor nodes. In addition to this, we also develop a distributed scheme to prevent the CHs from their quick death which is resulted from complete energy depletion. We perform extensive simulation on the proposed algorithms and compare the results with some existing algorithms to demonstrate its strength. Graphical abstract: